Al-Qur'an Memorization Learning Strategy in Forming the Character of Students at the Al-Jihad Student Islamic Boarding School in Surabaya - Muhaimin , Mohammad; El-Yunusi, M. Yusron Maulana (IJoIS: Indonesian Journal of Islamic Studies, 2024)
Promiscuity, violent crime, corruption, manipulation, fraud, and other disgraceful acts are some examples of the daily lives of people who have lost their morals. This shows bad behavior and despicable morals. The Arabic term "akhlaq" comes from the single word "khuluq", which means actions, both praiseworthy and despicable. Moral learning can be found in various educational institutions such as schools and especially in Islamic boarding schools, such as the Al-Jihad Islamic Boarding School in Surabaya. This research aims to find out the method of learning tahfidz Al-Qur'an and how it influences the character or morals of students, as well as how they are accepted and face challenges. This research uses a descriptive qualitative method, which means data is collected through a process of interviews, documentation and observation. There are three stages in analyzing data: condensing data, presenting data, and concluding. In this research, it was found that the Al-Quran tahfidz program at the Al-Jihad Surabaya student Islamic boarding school was carried out every Monday to Friday in the evening; On Saturdays at the end of each month, this program is only held in the morning. The activity begins by reading a prayer together. Then, people took turns coming forward to the listening ustadz to listen to the ziyadah or murojaah memorizing the Koran. The listening ustadz then assessed and encouraged them, and the activity closed with a group prayer. The existence of the tahfidz learning method forms a Qur'anic, skilled, intelligent and knowledgeable soul. They also become noble in character. Apart from the environment, lack of family attention, too much use of social media, and lack of self-encouragement, this tahfidz learning strategy faces many challenges. The strategy of learning Al-Quran tahfidz used at the Al-Jihad Surabaya student Islamic boarding school aims to produce students who are responsive, insightful, proficient and have noble behavior.